Activation of sodium persulfate by TiO2@MIL-101(Fe): Boosting the Fenton-like process by interfacial charge transfer. (February 2022) - Xu, Jiajie; Wang, Shengye; Yan, Changyu; Adeel Sharif, Hafiz Mohammad; Yang, Bo
Abstract: Advanced oxidation processes based on sulfate radicals are considered as a promising approach for environmental remediation. In this study, TiO2 @MIL-101(Fe) is successfully fabricated by a facile impregnation method and is used for sodium persulfate (SPS) activation. TiO2 @MIL-101@SPS combines the advantages of photocatalysis and SPS activation, which shows high removal efficiency for nitrobenzene and methyl orange. In addition, the effect of multiple factors, including light source, SPS amount and catalyst amount, on nitrobenzene degradation have been investigated. Results show that the nitrobenzene degradation efficiency is up to 66.53 % while that of TOC removal is 32.21 % under 4-h visible light irradiation with 30 mg catalyst and 1.6 mM SPS. Moreover, LC-MS have been carried out to study the route of nitrobenzene degradation. Besides, ESR analysis reveals that both ● SO4 − and ● OH radicals are generated sustainably under visible light irradiation, and more ● OH radicals can be detected owing to the synergic effect of photocatalysis and SPS activation. Interfacial charge transfer effect provides photoinduced electrons for the Fe 3+ /Fe 2+ cycle in MIL-101(Fe), which boosts the SPS activation process, resulting in high photocatalytic activity. Graphical abstract: Image 1 Highlights: TiO2 @MIL-101(Fe) is used for SPS activation under visible light irradiation. TiO2 @MIL-101@SPS combines the advantages of photocatalysis and SPS activation. Interfacial charge transfer effect could boost SPS activation process.